2005
DOI: 10.1007/s00438-005-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress

Abstract: More than 2,000 genome-wide barley single nucleotide polymorphisms (SNPs) were developed by resequencing unigene fragments from eight diverse accessions. The average genome-wide SNP frequency observed in 877 unigenes was 1 SNP per 200 bp. However, SNP frequency was highly variable with the least number of SNP and SNP haplotypes observed within European cultivated germplasm reflecting effects of breeding history on genetic diversity. More than 300 SNP loci were mapped genetically in three experimental mapping p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
200
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(215 citation statements)
references
References 82 publications
10
200
3
2
Order By: Relevance
“…The consensus map integrates already published (Saghai Maroof et al 1994;Becker and Heun 1995;Liu et al 1996;Struss and Plieske 1998;Ramsay et al 2000;Li et al 2003;Thiel et al 2003) and very recently developed (mainly GBM and scssr; Rostoks et al 2005;Varshney et al 2006a;Marcel et al 2007) barley SSR markers.…”
Section: Implications Of the Ssr Consensus Mapmentioning
confidence: 66%
See 2 more Smart Citations
“…The consensus map integrates already published (Saghai Maroof et al 1994;Becker and Heun 1995;Liu et al 1996;Struss and Plieske 1998;Ramsay et al 2000;Li et al 2003;Thiel et al 2003) and very recently developed (mainly GBM and scssr; Rostoks et al 2005;Varshney et al 2006a;Marcel et al 2007) barley SSR markers.…”
Section: Implications Of the Ssr Consensus Mapmentioning
confidence: 66%
“…Most of the markers mapped in the OWB population are AFLP markers, but the segregation data for 230 microsatellite loci could also be obtained (Table 1). Within the latter set of 230 microsatellite loci, 34 are new scssr (SCRI-SSR) loci recently integrated into a SNP map of barley (Rostoks et al 2005) and provided by Joanne Russell. Finally, the segregation data of 418 Liu et al (1996) Theor Appl Genet (2007) …”
Section: Ssr Markers and Segregation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In three cases, the chromosome location of the corresponding gene was known, providing a means to validate the spot segregation data. Thus, the gene encoding serpin Z7 is located on chromosome 5H (von WettsteinKnowles 1993), the gene encoding the α-amylase/trypsin inhibitor BMAI-1 is located on chromosome 2H (Mena et al 1992), and the barley grain peroxidase-encoding gene is found on chromosome 7H (Rostoks et al 2005). The known chromosome locations corresponded to group A (containing serpin Z7 spots), C (containing BMAI-1), B and M (containing barley grain peroxidase), respectively (Table 1, Supplementary Fig.…”
Section: Identification and Validation Of Snps In The Proteomementioning
confidence: 99%
“…In addition, this type of analysis can identify chromosome locations of transacting regulators of the proteins observed, as well as structural genes encoding the proteins themselves (Consoli et al 2002). Expression of the peroxidase gene on chromosome 7H was reported to be affected by abiotic stress (Rostoks et al 2005), and therefore, the presence or absence of the protein in different cultivars might be an indicator of stress tolerance.…”
Section: Identification and Validation Of Snps In The Proteomementioning
confidence: 99%